Development of solar still for water purification and its performance analysis - Siti Nudra Shafinie, Ab Aziz (2017)
Desalination process through solar still has been found to be the most economical technique, as it makes use of a free source of energy. The main drawback of this equipment is its low productivity. Thus, numerous enhancements have been developed throughout the years to improve its performance. In this study, the solar still underwent improvement using three simple enhancers, namely, aspirator, magnifying glasses (lenses), and heat transfer agent (HTA). Four sets of experiment were carried out to compare the performance of the solar still with different set-ups: Set 1 (aspirator), Set 2 (aspirator+ HTA), Set 3 (aspirator+ lenses) and Set 4 (aspirator +HTA +lenses). The experiment using the set with the highest efficiency was repeated with different feed which is seawater (Set 5). The highest collected evaporated volume was achieved by Set 4 at a total of 4.86 L while Set 1, Set 2 and Set 3 had a total of 0.68 L, 1.45 L and 3.43 L, respectively. The evaporation rates were proportional to the maximum instantaneous efficiency as Set 4 recorded the highest thermal efficiency of 70%, followed by Set 3, Set 2 and Set 1 with the percentage of efficiency at 51%, 42%, and 31%, respectively. For Set 5, the total collected evaporated volume is 4.23 L. Therefore, it can be concluded that although a slight improvement was observed, the effect of introducing the HTA was not significant. Nevertheless, if the HTA were combined with lenses in a vacuum solar still, the effect would be enormously significant. The water comparison analysis shows a very significant value between Set 4 and Set 5 at the initial state but small distinction at the final state. The results show that the performance of solar still increase significantly with the presence of lenses and HT A together. However, when the solar still is applied with HTA alone, only slight improvement is achieved compare to the application of lenses alone.